Uji Efektivitas Antibakteri Ekstrak Rimpang Kunyit (Curcuma domestica Val.) terhadap Pertumbuhan Propionibacterium acnes In Vitro - Annisa Cahyani; Dwi Indria Anggraini; Tri Umiana Soleha; Agustyas Tjiptaningrum (Jurnal Kesehatan, 2020)
One of the treatments for acne vulgaris therapy is antibiotics, it can be applied topically and systemically. However, long-term and inappropriate use of antibiotics can increase the incidence of antibiotic drug resistance. Some medicinal plants are known to have antimicrobial properties, one of them is turmeric rhizome. Turmeric rhizome is known to contain essential oils and curcumin so that it can be useful as an antibacterial, antiviral, anti protozoa, anti-inflammatory, antioxidant, and antineoplasm. This study aims to determine the effectiveness of the antibacterial turmeric extract against the growth of Propionibacterium acnes. The type of this research is an experimental laboratory with disc diffusion method on Mueller Hinton Agar media. Turmeric extract was obtained from the Laboratory of Organic Chemistry at the University of Lampung with maceration techniques using 96% ethanol. Turmeric rhizome extract is divided into several concentrations namely 15%, 30%, 50%, 75%, and 100%. As negative control is aquades and positive control is clindamycin. Data was obtained based on the result of measurement Diameter of inhibition zone made through paper discs and measured by calipers. The data were analyzed by using One Way ANOVA. The result of this study indicated that the diameter of the inhibits zone at a concentration of 15%, 30%, 50%, 75%, and 100%. Sequentially is 11,35mm, 15,65mm, 17,575mm, 18,85mm, and 20,8mm. in the negative control is 0 mm and positive control is 28,1 mm (score p-value=0,000). There is antibacterial effectiveness of turmeric extract against the growth of Propionibacterium acnes in vitro, but it is no superior compared with clindamycin phosphate.